Suffering in the Perspective of Being Religious - Wiryadinata, Halim (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2025)
Humans and suffering are inseparable because they complement each other throughout life. Basically, humans, as weak creatures, always seek religion as external guidance to support their lives. Therefore, we assert that religious premises serve as external power to help humans survive suffering by building an understanding of religion and suffering from the perspective of religious sociology and by offering an argument for how Job accepted suffering to show himself to be a religious man. In the last part of our paper, we will show that suffering forms a man as a religious man in the faith growth as part of the human life process.